Temporary amnesia from sleep loss: A framework for understanding consequences of sleep deprivation - Whitney, Paul; Kurinec, Courtney A.; Hinson, John M. (Frontiers in Neuroscience, 2023)
Throughout its modern history, sleep research has been concerned with both the benefits of sleep and the deleterious impact of sleep disruption for cognition, behavior, and performance. When more specifically examining the impact of sleep on memory and learning, however, research has overwhelmingly focused on how sleep following learning facilitates memory, with less attention paid to how lack of sleep prior to learning can disrupt subsequent memory. Although this imbalance in research emphasis is being more frequently addressed by current investigators, there is a need for a more organized approach to examining the effect of sleep deprivation before learning. The present review briefly describes the generally accepted approach to analyzing effects of sleep deprivation on subsequent memory and learning by means of its effects on encoding. Then, we suggest an alternative framework with which to understand sleep loss and memory in terms of temporary amnesia from sleep loss (TASL). The review covers the well-characterized properties of amnesia arising from medial temporal lobe lesions and shows how the pattern of preserved and impaired aspects of memory in amnesia may also be appearing during sleep loss. The view of the TASL framework is that amnesia and the amnesia-like deficits observed during sleep deprivation not only affect memory processes but will also be apparent in cognitive processes that rely on those memory processes, such as decision-making. Adoption of the TASL framework encourages movement away from traditional explanations based on narrowly defined domains of memory functioning, such as encoding, and taking instead a more expansive view of how brain structures that support memory, such as the hippocampus, interact with higher structures, such as the prefrontal cortex, to produce complex cognition and behavioral performance, and how this interaction may be compromised by sleep disruption.